2017
DOI: 10.24925/turjaf.v5i4.326-334.1210
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Honey Using New Generation Infrared Spectrometers

Abstract: The objective of this study was to develop a rapid infrared technique to determine 10 key quality parameters (sucrose, glucose, fructose, reducing sugar, 5-HMF, °Brix, moisture content, water activity, pH and free acidity) in honey by using new generation portable and handheld devices. The composition of honey samples (n=59) collected from different parts of Turkey was analyzed by using established reference methods, giving wide range of concentrations for each parameter. The levels of sucrose and 5-HMF in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
5
5
0
1
Order By: Relevance
“…Honey samples showed aw values lower than 0.7 (0.7 is the limit for pathogen bacterial growth) (Jay, 2007). This data is in agreement with those reported from several Authors that reported aw mean values for honey ranging from 0.47 to 0.64 (Ayvaz, 2017;Manzanares, García, Gald on, Rodríguez-Rodríguez, & Romero, 2017;Olaitan, Adeleke, & Ola, 2007). The values of aw resulted also lower than 0.61, critical value for osmopholic yeast growth, that ensure relatively long shelf life of the honey samples (Ayvaz, 2017;Gleiter, Horn, & Isengard, 2006;Zamora & Chirife, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Honey samples showed aw values lower than 0.7 (0.7 is the limit for pathogen bacterial growth) (Jay, 2007). This data is in agreement with those reported from several Authors that reported aw mean values for honey ranging from 0.47 to 0.64 (Ayvaz, 2017;Manzanares, García, Gald on, Rodríguez-Rodríguez, & Romero, 2017;Olaitan, Adeleke, & Ola, 2007). The values of aw resulted also lower than 0.61, critical value for osmopholic yeast growth, that ensure relatively long shelf life of the honey samples (Ayvaz, 2017;Gleiter, Horn, & Isengard, 2006;Zamora & Chirife, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The values in literature are higher comparing to our study and the difference may be dependent on botanical and geographical origin of the samples. Ayvaz [33] found the refractive index in the range from 1.49 to 1.51 in Turkish honey. Italian scientists showed that royal jelly samples had refraction index scattered in the range 1.38-1.40 [34].…”
Section: Physicochemical Properties Of Bee Pollen and Other Bee Productsmentioning
confidence: 99%
“…Upravo zato, imperativ je odrediti pravilan kriterij kontrole kvalitete da bi potrošači konzumirali kvalitetniji i zdraviji proizvod (Ayvaz, 2017. )…”
Section: Uvodunclassified